Sex differences in the prognosis of patients with hypertrophic cardiomyopathy - Minkwan Kim (Nature Portfolio, 2021)
Abstract We investigated sex-related differences in the prognosis of patients with hypertrophic cardiomyopathy (HCM) using the Korea National Health Insurance Service database. From 2010 to 2016, 9524 patients diagnosed with HCM and had more than 1-year follow-up period were analyzed. The primary endpoint was the composite of cardiovascular death or new-onset heart failure (HF) admission. Propensity score-matching analysis was performed to adjust for different baseline characteristics. With a 4.4-years’ median follow-up interval (range 2.0–6.6 years) and male predominance (77.6%), women with HCM were older (52.6 ± 9.7 vs. 51.4 ± 9.1, p < 0.001), had lower incomes, more comorbidities based on Charlson comorbidity index. Women with HCM had a higher incidence of the primary endpoint than men (incidence rate: 34.15 vs. 22.83 per 1000 person-years, log-rank p < 0.001). Multivariable Cox analysis showed that female sex was a poor prognostic factor for the primary endpoint (HR 1.43, 95% CI 1.24–1.64, p < 0.001). This was mainly driven by a higher incidence of new-onset HF admission (HR 1.55, 95% CI 1.34–1.80). However, there was no difference in the incidence of cardiovascular death between the sexes. This result was concordant in the propensity score-matched cohort. In conclusion, women with HCM have worse prognosis, which was mainly driven by a higher new-onset HF admission.